A robust seeding technique for the growth of single grain (RE)BCO and (RE)BCO–Ag bulk superconductors. (27th February 2018) - Namburi, Devendra K; Shi, Yunhua; Dennis, Anthony R; Durrell, John H; Cardwell, David A
Abstract: Bulk, single grains of RE–Ba–Cu–O [(RE)BCO] high temperature superconductors have significant potential for a wide range of applications, including trapped field magnets, energy storage flywheels, superconducting mixers and magnetic separators. One of the main challenges in the production of these materials by the so-called top seeded melt growth technique is the reliable seeding of large, single grains, which are required for high field applications. A chemically aggressive liquid phase comprising of BaCuO2 and CuO is generated during the single grain growth process, which comes into direct contact with the seed crystal either instantaneously or via infiltration through a buffer pellet, if employed in the process. This can cause either partial or complete melting of the seed, leading subsequently to growth failure. Here, the underlying mechanisms of seed crystal melting and the role of seed porosity in the single grain growth process are investigated. We identify seed porosity as a key limitation in the reliable and successful fabrication of large grain (RE)BCO bulk superconductors for the first time, and propose the use of Mg-doped NdBCO generic seeds fabricated via the infiltration growth technique to reduce the effects of seed porosity on the melt growth process. Finally, we demonstrate that the use of such seeds leads to better resistance to melting during the single grain growth process, and therefore to a more reliable fabrication technique.